1985
DOI: 10.1148/radiology.154.2.3155569
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse pulmonary hemorrhage: a review and classification.

Abstract: Diffuse pulmonary hemorrhage is an uncommon condition that is difficult to differentiate radiographically from diffuse pneumonia or pulmonary edema. The diagnosis should be suspected when a patient has even mild hemoptysis or has one of the diseases known to be associated with diffuse pulmonary hemorrhage. This paper reviews the clinical and radiographic features of diffuse pulmonary hemorrhage and presents a classification scheme depicted as a Venn diagram formed by four overlapping circles representing pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
7

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 0 publications
0
36
0
7
Order By: Relevance
“…in the review literature, a few reviews suggest that leptospirosis should be considered. 24,25 However, our results showed that congestion pulmonary and hemorrhage areas were present in histopatologic findings, and there was pulmonary involvement in leptospirosis. Two main mechanisms of leptospirosis pathogenesis are suggested: a toxin-mediated mechanism and/or the immune responses of the host.…”
Section: Discussionmentioning
confidence: 49%
“…in the review literature, a few reviews suggest that leptospirosis should be considered. 24,25 However, our results showed that congestion pulmonary and hemorrhage areas were present in histopatologic findings, and there was pulmonary involvement in leptospirosis. Two main mechanisms of leptospirosis pathogenesis are suggested: a toxin-mediated mechanism and/or the immune responses of the host.…”
Section: Discussionmentioning
confidence: 49%
“…Pulmonary-renal syndromes that may cause pulmonary hemorrhage include Goodpasture's syndrome, Wegener's granulomatosis, systemic lupus erythematosus, Henoch-Schonlein purpura, mixed connective-tissue disease, and other vasculitis (14). Other causes of pulmonary hemorrhage include anticoagulant therapies, disseminated intravascular coagulation, thrombocytopenia, leukemia, acute lung injury, aspiration of blood, drug toxicity, traumas, and mitral stenosis (19). CT scans may show consolidation with GGO and interlobular septal thickening, as well as a halo of GGO around a focal area of lung consolidation.…”
Section: Pulmonary Hemorrhagementioning
confidence: 99%
“…Hemorragia alveolar difusa é uma expressão utilizada na literatura médica atual para se referir a uma síndrome clinicopatológica caracterizada por sangramentos que se originam na microvasculatura pulmonar (Dweik et al 1997). Assim como outras sín-dromes, a hemorragia alveolar difusa é simplesmente uma manifestação de diversas doenças e o processo comum a todas elas é o sangramento intra-alveolar difuso (Albelda et al 1985, Schwarz et al 1994, quase sempre decorrente de capilarite (Lara & Schwarz 2010).…”
Section: Discussionunclassified